An ongoing process of reconnection: A qualitative exploration of mindfulness‐based cognitive therapy for adults in remission from depression. (17th July 2021) - Williams, Kate; Hartley, Samantha; Anderson, Ian M.; Birtwell, Kelly; Dowson, Merryn; Elliott, Rebecca; Taylor, Peter
Abstract : Objectives: Mindfulness‐based cognitive therapy (MBCT) is an 8‐week relapse‐prevention intervention designed for people who have experienced multiple episodes of depression and remain vulnerable to relapse. Previous qualitative explorations of the effects of MBCT for people in remission from depression have suggested a number of themes regarding changes arising from participating in MBCT ranging from awareness, agency, perspective, group processes, self‐related change, and new ways of understanding depression. We aimed to qualitatively explore how participants in remission from depression experienced MBCT both post‐MBCT and during a follow‐up period. Methods: In a preference‐choice trial design, 35 participants took part in qualitative interviews and assessments post‐MBCT and at three time points during a 12‐month follow‐up. Data were analysed using reflexive thematic analysis. Results: Two overarching themes were developed as follows: (1) 'reconnection with experience, self, and others' and (2) 'acknowledging an ongoing process of change'. In theme one, sub‐themes captured participants' experiences of increasing levels of awareness of their experience (e.g., thoughts, emotions, sensations, and present moment) from which they described changes in their relationship with experience describing increases in control, choice, acceptance, and calm. Participants described shifts towards reconnection with aspects of the self and relationships with others. In theme two, sub‐themes reflected participants' conflict between avoidance and engagement in mindfulness practices, and the recognition of the gradual change following MBCT and long‐term investment needed in mindfulness practices. Conclusions: Our findings have clinical implications in terms of facilitating MBCT and point to important themes around recognizing the ongoing process of reconnection with experiences, self, and others. Practitioner points: Participants with histories of depression may have experienced disconnection and isolation from internal experiences (e.g., thoughts and emotions), self, and others; MBCT encourages a deliberate shift towards reconnection with these experiences. Practitioners could encourage more psychoeducation and discussions around depression during MBCT to encourage reflections on the process of reconnection. Practitioners should maintain an awareness of the ongoing, gradual processes of change and potential for conflict experienced during MBCT Practitioners could provide a stronger emphasis on building awareness of body sensations during MBCT, with suggestions provided in the discussion section.